Comparative study of force control methods for bipedal walking using a force-sensitive hydraulic humanoid. (16th November 2020) - Murotani, Kazuya; Yamamoto, Ko; Ishigaki, Taiki; Nakamura, Yoshihiko
ABSTRACT: This paper describes an experimental comparison of force control methods, including resolved acceleration control (RAC), joint position control (JPC), and resolved viscoelasticity control (RVC), focusing on the biped walking performance. In previous studies, we reported a stable biped walking using the JPC and RVC methods on a hydrostatically driven humanoid, Hydra. All joints of Hydra are actuated by electro-hydrostatic actuators, showing the high backdrivability and force-controllability. However, we did not realize the RAC on Hydra, which is a standard method in state-of-the-art humanoid robotics. It is the first time that we have reported the RAC method realized a biped walking on Hydra. Moreover, the comparison between three methods is presented. GRAPHICAL ABSTRACT: UF0001